Comments by Tan Dun on His Music - Mativetsky, Shawn (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2002)
Guest of honour at the Musimarch 2002 festival at McGill University, Montreal, the Chinese composer Tan Dun gave, amongst others, a conference on his music that developed into a passionate dialogue with the audience. We have transcribed his ideas on his music, his influences, his personal development and his impressions on Western music.